The implementation of metacognitive strategies in writing a thesis - Mahalli, Mahalli; Candraloka, Olivia; Sa’diyah, Khalimatus; Sukarman, Sukarman (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
Empirical evidence reveals that a common obstacle for students in writing a thesis is that they have difficulties in writing literature reviews, formulating a thesis topic or problem, and writing the contents of their thesis. The research was conducted to investigate metacognitive strategies and their impact on writing students’ theses. The research was conducted at the Islamic University of Nahdlatul Ulama (UNISNU) in Jepara. A case study research design guided this research. The participants involved were 30 students, comprising 20 women and 10 men, and the study included semi-structured interviews with 3 thesis supervisors. The findings reveal two main things. First, in the process of using metacognitive strategies, students map and develop writing concepts. Students are guided to compose various effective sentences, elaborating the introduction, main, and conclusion parts of the thesis in detail. Second, in terms of the impact of metacognitive skills, students can understand the contents of the thesis and recognise the characteristics of academic writing, writing procedures, and requirements for selecting topics. It can be concluded that students' metacognitive abilities contribute to the development of quality thesis writing skills.